1983
DOI: 10.1161/01.hyp.5.6_pt_3.v138
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of cardiovascular disease events by worksite hypertension treatment.

Abstract: SUMMARY A retrospective cohort study of hypertensive employees to evaluate the impact of worksite antihypertensive treatment (WST) on cardiovascular disease (CVD) over S'/i years is reported. In a union-sponsored screening from August 1973 to February 1974 hypertensives (S= 160 and/or 95 mm Hg, or on medication) were identified. Of these, standardized criteria were met by 344, of whom 150 chose WST and 194 referred care (RC). The study groups were similar in age and sex composition. Union hospitalization and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

1986
1986
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 15 publications
0
10
0
1
Order By: Relevance
“…Several studies have demonstratet that when a work health service has adequate equipment and facilities -either of its own or through its connection with other health services outside the company (16) -controlling hypertension in the workplace considerably reduces the indirect costs (TWI, permanent disability and mortality) caused by this disorder, and benefits not only the company and its workers but also public health in general (1,2,8,9,11). It also has, however, certain advantages over other environments, that is, the accessibility of employees, their familiarity with the health service, cost reduction, and more (15).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstratet that when a work health service has adequate equipment and facilities -either of its own or through its connection with other health services outside the company (16) -controlling hypertension in the workplace considerably reduces the indirect costs (TWI, permanent disability and mortality) caused by this disorder, and benefits not only the company and its workers but also public health in general (1,2,8,9,11). It also has, however, certain advantages over other environments, that is, the accessibility of employees, their familiarity with the health service, cost reduction, and more (15).…”
Section: Resultsmentioning
confidence: 99%
“…their place of work, not only for reasons of effectiveness (in determining influencing factors and/ or results) but also from the point of view of the efficiency (cost reduction) of the programs (1,2,6,8,9,11). their place of work, not only for reasons of effectiveness (in determining influencing factors and/ or results) but also from the point of view of the efficiency (cost reduction) of the programs (1,2,6,8,9,11).…”
Section: Introductionmentioning
confidence: 99%
“…The range of endogenous plasma irANF concentration was determined in peripheral venous blood from 70 normal volunteers derived from a previously characterized defined population (24), who were studied in the seated position while on a regular diet; and 31 patients with congestive heart failure on standard digoxin and diuretic therapy. In seven supine normal subjects undergoing hemodynamic study (protocol II), simultaneous blood samples were obtained from a peripheral vein and from the right ventricle.…”
Section: Glossarymentioning
confidence: 99%
“…In a randomized controlled trial, Kaczorowski and colleagues demonstrated that a community‐based BP screening program that included cardiovascular risk assessment and education sessions reduced cardiovascular morbidity and mortality . Additionally, there is evidence to suggest that once high BP is controlled in screened individuals, there is improvement in quality of life and work absenteeism . However, there are no standardized approaches to assist in the development of community‐based BP screening programs in LRS.…”
Section: Global Burden Of Hypertensionmentioning
confidence: 99%
“…13 Additionally, there is evidence to suggest that once high BP is controlled in screened individuals, there is improvement in quality of life and work absenteeism. [14][15][16] However, there are no standardized approaches to assist in the development of communitybased BP screening programs in LRS.The systematic reviews from the CTFPHC and USPSTF found scant literature on screening programs in LRS. 10,11 While describing the Canadian landscape, Lindsay and colleagues 5 demonstrated a higher…”
mentioning
confidence: 99%